Rose Rosette Disease Resistance Loci Detected in Two Interconnected Tetraploid Garden Rose Populations - Lau, Jeekin; Young, Ellen L.; Collins, Sara; Windham, Mark T.; Klein, Patricia E.; Byrne, David H.; Riera-Lizarazu, Oscar (Frontiers in Plant Science, 2022)
Rose rosette disease (RRD), caused by the Rose rosette emaravirus (RRV), is a major threat to the garden rose industry in the U.S.A. There has been limited work on the genetics of host plant resistance to RRV. Two interconnected tetraploid garden rose F1 bi-parental mapping populations were created to develop high-quality tetraploid rose linkage maps that allowed the discovery of RRD resistance quantitative trait loci (QTL) on linkage groups (LGs) 5, 6, and 7. These QTL individually accounted for around 18-40% of the phenotypic variance. The locus with the greatest effect on partial resistance was found in LG 5. Most individuals with the LG 5 QTL were in the simplex configuration, however, two individuals were duplex (likely due to double reduction). Identification of resistant individuals and regions of interest can help the development of diagnostic markers for marker assisted selection in a breeding program.